THE USE OF MASK AND STRETCHING THE SHAF OF JUSTICE PRAYERS IN THE PANDEMIC PERIOD IN MUI FATWA NUMBER 31 OF 2020: QAWAID FIQHIYYAH PERSPECTIVE - Zainuddin Puteh; Dhiauddin Tanjung (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2022)
On June 4 2020, the Indonesian Ulema Council (MUI) issued fatwa Number 31 of 2020 concerning "Organization of Friday and Congregational Prayers to Prevent the Transmission of the Covid-19 Outbreak. The fatwa then became the object of scientific study from various perspectives, including regarding prayers using masks and stretching the shaf when praying in congregation. However, no one has yet discussed the relevance and accuracy of the fiqh principles used in fatwas. In fact, the principles of fiqh are one of the normative dimensions of Islamic law which are directly related to practical situations. For this reason, the author feels the need to make aspects of fiqh principles in fatwa as study material - so that the discussion is carried out in a normative (doctrinal) way. After reviewing, the author concludes that the principles used in the fatwa are very relevant and accurate. Therefore, praying using a mask and stretching the shaf is a very appropriate fatwa, because this fulfills the elements of a syar'i intention, namely an endeavor to break the chain of the spread of the life-threatening Covid-19 pandemic